Efektivitas Terapi Psiko Spiritual Terhadap Penurunan Tingkat Kecemasan Pada Pasien Tuberculosis Paru Dengan Terapi Obat - Muhammad Amrullah; Alon Ekawati; M. Rizam Umami (Institut Citra Internasional, 2021)
Background: Psycho-spiritual therapy is a therapy based on spiritual factors that is used to increase an individual's faith in God to increase immunity and endurance in dealing with various problems. The research objective was to determine the effectiveness of deep breath dzikir psycho-spiritual therapy in reducing anxiety levels in pulmonary tuberculosis patients. This research was conducted on 15-19 September 2020. Research Methods: This study used a Pre Experimental method using the One Group Pre-Post test design approach. The sampling technique used is non probability sampling, namely incidental sampling. Population of 28 people with a total sample of 21 people with anxiety. Data analysis using t-test. Research rsults: The results of the t-test statistical test showed that the effectiveness of psycho-spiritual therapy in reducing anxiety levels in patients with pulmonary tuberculosis with OAT therapy p value = 0.001, which means that the p value <0.05 means that Ho is rejected and Ha is accepted. Conclusion: There is an effect of psycho-spiritual therapy on reducing anxiety levels in pulmonary tuberculosis patients with OAT therapy.